Experimental Investigation of the Photochemical Production of Hydrocarbons in Warm Gas Giant Exoplanet Atmospheres - Benjamin Fleury; Yves Benilan; Olivia Venot; Bryana L. Henderson; Mark Swain; Murthy S. Gudipati (The Astrophysical Journal, 2023)
In warm (equilibrium temperature <1000 K) gas giant exoplanet atmospheres, the observation of trace species in abundances deviating from thermochemical equilibrium predictions could be used as an indicator of disequilibrium chemical processes, such as photochemistry. To predict which compounds could be used as such tracers, it is therefore essential to study how photochemical processes affect their abundances. For this purpose, we investigated experimentally the efficiency of the photochemical formation of hydrocarbons in gas mixtures representative of warm gas giant atmospheres as a function of the gas temperature at millibar pressures. We find that, compared to thermal reactions alone, photochemistry efficiently promotes, under the studied conditions, the formation of hydrocarbons, with the detection of acetylene, ethane, and propane, as well as carbon monoxide. Therefore, our results confirm the importance of photochemistry in exoplanet atmospheres as a disequilibrium process. Ethane is the major hydrocarbon formed in our experiments, in apparent contradiction with the prediction by thermo-photochemical models that acetylene should be the main hydrocarbon product. We also observe an evolution of the hydrocarbon production efficiency as a function of the temperature, a behavior not reproduced by a 0D thermo-photochemical model. Additional studies are necessary to definitively understand the origin of the differences between the experimental and modeling results and to infer the importance of our results for understanding hydrocarbon formation in warm gas giant exoplanet atmospheres. Finally, our work demonstrates the importance of experimental studies together with modeling studies to accurately interpret, understand, and predict observations of exoplanet atmospheres.